Advances in Supply Chain Coordination : A Bibliometric Review of Coordination Mechanisms, Technologies, and Emerging Trends - Veeresh Tripathi, Sandeep Mondal (European Economic Letters (EEL), 2025)
Purpose – Supply chain coordination is crucial to organizational performance and is a major challenge. This study performs a bibliometric review of SCC literature over the last 20 years, examining articles to determine coordination methods, problems, trends, and suggestions for improving supply chain performance. Design/methodology/approach – A bibliometric analysis of 1997 publications from 2003 to 2023 was performed using VOSviewer for author, citation, and keyword co-occurrence visualization. A systematic review of highly cited SCC studies was used to determine coordination mechanisms in practice. Findings – The research defines five coordination mechanisms: (1) Supply Chain Contracts, (2) Information Sharing, (3) Joint Decision-making, (4) Information Technology, and (5) Emerging Technologies. It discovers a large body of research on SCC but notes gaps in cross-industry implementation and the integration of new technologies. Research limitations/implications - This study relies solely on the Web of Science Database for citation information, and some important research could be left out. Moreover, it provides one point of reference for researchers and experts for improved SCC. Practical implications – Supply chain managers can learn from this research on coordination mechanisms and performance. It provides insights for future studies, especially to the service sector and consulting organizations embracing new technology. Social implications – Improved coordination across supply chain networks will ensure maximum resource utilization, hence higher profitability and enhanced service reach., benefiting both the organizations and society. Originality/value – The paper provides bibliometric insights on two decades' worth of SCC literature, concluding with common coordination mechanisms for supply chain performance. It is a guide for practitioners and scholars with prevailing trends and future research directions.